BENTUK KOREOGRAFI TORTOR ILAH MARDIDONG DI KABUPATEN SIMALUNGUN - Kheliana Kheliana (Universitas Negeri Medan, 2016)
Tor -tor dance IlahMardidong is growing and developing in Simalungun . Tor- tordance is a tradition that has been rearranged forms of the movement in 1985 by aman named Lina Br Damanik . The purpose of this study is to discuss the tor-torIlahMardidong viewed from the standpoint of choreographic form.The theory used in this research is the theory of Forms choreography Sudarsonowhich contains about : motion , theme , design floors , top design, fashion andmusic . This theory became a reference for peeling the existing problems in thetor- tor god mardidong .When the study to discuss IlahMardidong dance performed during 3 months ,iefrom the beginning of October 2015 through December 2015. The study in thevillage of Huta III Glare Malela . Glare SubdistrictMalela . The population is threepersons namely speakers , traditional leaders , and artists who know about theculture Simalungun . samples in this study were of three persons namely speakers, traditional leaders and artists in Simalungun . Data collection techniquesincluding observation , interviews , literature study and documentation , which isthen analyzed by qualitative descriptive method .Based on research done that tor-tor IlahMardidong have a soft form of motion,tortorIlahMardidong wear internal musical accompaniment is music that is bornout of the human body . Clothing used in this Tortor is yeast pane ,surisuri andheaddress silappei . The themes contained in this dance is the hope of a mother forher child , and the top design contained in this dance is the design in the design,low design and asymmetrical design .